2014
DOI: 10.1016/j.brs.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The Uncertain Outcome of Prefrontal tDCS

Abstract: Background Transcranial direct current stimulation (tDCS) is increasingly used in research and clinical settings, and the dorsolateral prefrontal cortex (DLPFC) is often chosen as a target for stimulation. While numerous studies report modulation of cognitive abilities following DLPFC stimulation, the wide array of cognitive functions that can be modulated makes it difficult to predict its precise outcome. Objective The present review aims at identifying and characterizing the various cognitive domains affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
164
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(175 citation statements)
references
References 88 publications
(119 reference statements)
6
164
1
4
Order By: Relevance
“…In many motor studies, TMS is used to precisely locate target areas in the motor cortex and directly measure tDCS-induced changes in cortical excitability through the amplitude of motor-evoked potentials (MEPs). Localization of nonmotor targets, in contrast, is much less precise and any cognitive task is likely to involve a number of cortical areas making it difficult to attribute performance changes to stimulation of a specific cortical region (Tremblay et al, 2014). These factors may have contributed to the lower effect size associated with studies of cognitive function.…”
Section: Meta-analytic Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many motor studies, TMS is used to precisely locate target areas in the motor cortex and directly measure tDCS-induced changes in cortical excitability through the amplitude of motor-evoked potentials (MEPs). Localization of nonmotor targets, in contrast, is much less precise and any cognitive task is likely to involve a number of cortical areas making it difficult to attribute performance changes to stimulation of a specific cortical region (Tremblay et al, 2014). These factors may have contributed to the lower effect size associated with studies of cognitive function.…”
Section: Meta-analytic Findingsmentioning
confidence: 99%
“…However, a caveat to this conclusion is warranted. A recent review of 61 studies applying tDCS to the DLPFC found a lack of consistency in outcomes making causal conclusions between DLFPC stimulation and a particular cognitive function difficult (Tremblay et al, 2014). One reason for the inconsistency is that tDCS appears to simultaneously modulate activity in a number of brain areas subserving a variety of cognitive functions with the maximum field strength being located some distance (20-40 mm) from the target area (e.g., DLPFC) (Rampersad et al, 2014).…”
Section: Meta-analytic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of tDCS over the prefrontal cortex in nonneuropsychiatric samples have yielded mixed results [25]. The lack of effects in the hot working memory task might also be explained by a "ceiling" effect in healthy samples that already adequately process emotional content, leaving little room for improvement for the task.…”
Section: Discussionmentioning
confidence: 99%
“…Viewing the literature as a whole, there are concerns about the replicability of tDCS findings. For example, tDCS of left DLPFC, using the same electrode montage as the authors, is sometimes associated with increases in working memory capacity and other times with decreases (18). Moreover, Horvath et al (19) suggested that the cognitive effects of single-session tDCS may have been overstated and that neurophysiological effects may not extend beyond enhancement of motor-evoked potentials (20).…”
mentioning
confidence: 94%